SPE/DOE Symposium on Improved Oil Recovery 2004
DOI: 10.2118/89466-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measured Z-Factor of CO2–Dry Gas/Wet Gas/Gas Condensates for CO2 Storage in Depleted Gas Reservoirs

Abstract: In support of the research project at the Center for Applied Petrophysical and Reservoir Studies in geologic storage of carbon dioxide in depleted gas reservoirs, the PVT laboratory at Texas Tech University performed compressibility factor (z-factor) measurements at various composition of CO2 with hydrocarbon (HC) gas mixture. For the sole purpose of the measured Z-factor data, three temperatures of 100°F, 160°F and 220°F and pressures ranges from 50 psia to 5000 psia are selected as representative of the depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In the first step, the composition of dry, wet, and condensate gas at the depleted stage was taken from the literature . Adisoemarta et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first step, the composition of dry, wet, and condensate gas at the depleted stage was taken from the literature . Adisoemarta et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, the composition of dry, wet, and condensate gas at the depleted stage was taken from the literature . Adisoemarta et al . used these compositions to calculate the compressibility factor for storage purposes in depleted gas reservoirs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adisoemarta et al (2004) performed measured compressibility factors, z-factor, for various mixtures of CO 2 and natural gas. They concluded that zfactor for the mixture is much lower than natural gas at the specified temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%